EMPLOYEE ENGAGEMENT: THE ROLE OF TRANSFORMATIONAL LEADERSHIP, WORK ENVIRONMENT, AND JOB SATISFACTION - Sutanto, Eddy; Santoso, Thomas; Halim, Kevin (TRIKONOMIKA, 2025)
This research is crucial for understanding how transformational leadership, a supportive work environment, and job satisfaction collectively enhance employee engagement, an essential factor for driving organizational performance, especially in today’s dynamic and evolving workplace. The study offers practical insights for leaders aiming to foster a more motivated, committed, and high-performing workforce.  It was conducted to see whether transformational leadership and work environment influenced employee engagement with job satisfaction as a mediating variable. The research method was a quantitative study with a purposive sampling technique, with 179 respondents. The data for this research was processed using SmartPLS 3.0. The results showed that transformational leadership and work environment had a positive and significant effect on job satisfaction and employee engagement, job satisfaction had a positive and significant impact on employee engagement, and job satisfaction positively and significantly mediated the effect of transformational leadership and work environment on employee engagement.